RabGTD: a comprehensive database of rabbit genome and transcriptome. (13th July 2018) - Zhou, Lu; Xiao, Qingyu; Bi, Jie; Wang, Zhen; Li, Yixue
Abstract: The rabbit is a very important species for both biomedical research and agriculture animal breeding. They are not only the most-used experimental animals for the production of antibodies, but also widely used for studying a variety of human diseases. Here we developed RabGTD, the first comprehensive rabbit database containing both genome and transcriptome data generated by next-generation sequencing. Genomic variations coming from 79 samples were identified and annotated, including 33 samples of wild rabbits and 46 samples of domestic rabbits with diverse populations. Gene expression profiles of 86 tissue samples were complied, including those from the most commonly used models for hyperlipidemia and atherosclerosis. RabGTD is a web-based and open-access resource, which also provides convenient functions and friendly interfaces of searching, browsing and downloading for users to explore the big data. Database URL: http://www.picb.ac.cn/RabGTD/